Expert Office 365 : notes from the field - Charlebois-Laprade, Nikolas (Apress, 2017)
Get to grips with Office 365 through in-depth tutorials and insights from leading experts. Topics covered include Exchange Online, SharePoint Online, Skype Online, and more. This deeply technical book tackles key aspects of online collaboration and business productivity within Office 365. Expert Office 365 is written by a dedicated team of Microsoft Premier Field Engineers (PFEs), and captures advice, best practices, and insights from their experience in the field. What You'll Learn: Develop client Web Parts with the new SharePoint Framework Create a recovery plan for SharePoint Online Configure SharePoint Online Hybrid Search and Portals Configure and optimize Exchange Online Optimize collaboration in your organization through analytics insights.